Hubungan kualitas darah dengan konsentrasi transforming growth factor-β pada platelet rich plasma yang digunakan untuk regenerasi tulang dan jaringan periodontal (Correlation of blood quality with concentration of transforming growth factor-ß1 in platelet rich plasma for bone and periodontal tissue regeneration) - Surijana Mappangara; Burhanuddin DP; Arni Irawaty Djais (Journal of Dentomaxillofacial Science, 2014)
This study aimed to explore the correlation of blood quality with transforming growth factor (TGF-ß1) of platelet richplasma (PRP) which was used for bone and periodontal tissue regeneration. Thirty nine subjects participated in thisstudy. Data of age, gender, eritrocyt, leucocyt, hemoglobin, thrombocyt, and TGF-ß1 concentration were used toanalyze the correlation using Spearman correlation test. This study found leucocyt, eritrocyt, hemoglobin, thrombocytconcentration mean was 8.19 g/dl, 5.31 g/dl, 14.48 g/dl, 326.32 g/dl, respectively. The TGF-ß1 concentration meanacquired from PRP was 31994.27 pg/ml. Based on Spearman correlation test, significant correlation was onlyobserved in eritrocyt concentration variable with p value 0.023 (p<0.05) and it was higher in male than in female. It was concluded that TGF-ß1 concentration in PRP from normal subject was 31994.27 pg/ml. Based on leucocyt,eritrocyt, hemoglobin, and thrombocyt test to TGF-ß1, only eritrocyt showed the significant relationship. This findingalso showed the linear correlation between the amoung of eritrocyt in blood with TGF-ß1 as the increased eritrocytvalue was followed by the excalated TGF-ß1 value.